2021
DOI: 10.3390/nano11040868
|View full text |Cite
|
Sign up to set email alerts
|

Towards Clinical Translation: Optimized Fabrication of Controlled Nanostructures on Implant-Relevant Curved Zirconium Surfaces

Abstract: Anodization enables fabrication of controlled nanotopographies on Ti implants to offer tailorable bioactivity and local therapy. However, anodization of Zr implants to fabricate ZrO2 nanostructures remains underexplored and are limited to the modification of easy-to-manage flat Zr foils, which do not represent the shape of clinically used implants. In this pioneering study, we report extensive optimization of various nanostructures on implant-relevant micro-rough Zr curved surfaces, bringing this technology cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Recent attempts to optimize EA to enable clinical translation include fabrication of controlled nanostructures on clinical dental implants [36], superior mechanical stability (nanopores > nanotubes) [37], and fabrication of dual micro-nano structures [38] by preserving the underlying 'gold standard' micro-roughness of dental implants [39]. It is worth noting that EA is a versatile technique that can be used to nano-engineer controlled topographies on various biomedical implants, spanning various metals and alloys, including Ti [40], Ti alloys [41], Zr [42] and Al [43]. A schematic representation of TNTs and their various characteristics and research challenges is shown in Figure 1.…”
Section: Nanoscale Dental Implant Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent attempts to optimize EA to enable clinical translation include fabrication of controlled nanostructures on clinical dental implants [36], superior mechanical stability (nanopores > nanotubes) [37], and fabrication of dual micro-nano structures [38] by preserving the underlying 'gold standard' micro-roughness of dental implants [39]. It is worth noting that EA is a versatile technique that can be used to nano-engineer controlled topographies on various biomedical implants, spanning various metals and alloys, including Ti [40], Ti alloys [41], Zr [42] and Al [43]. A schematic representation of TNTs and their various characteristics and research challenges is shown in Figure 1.…”
Section: Nanoscale Dental Implant Modificationsmentioning
confidence: 99%
“…Zirconium (Zr) and zirconia (ZrO 2 ) are rising as dental implant material choices due to their biocompatibility, corrosion resistance and superior mechanical properties [42]. It is established that Zr 4+ ions can interact with negatively charged bacterial membranes and cause cell damage and death [148].…”
Section: Zirconiamentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In order to develop nanotubes on such surfaces, multi-step procedures start with metal deposition on the parent materials via vacuum assisted treatments such as ALD, e-beam sputtering, FDM, etc. [8][9][10][11] This technique poses numerous challenges such as adhesion of metal to substrate, stability at the interface in addition to the cost-factor to name few. The latest growing trend in biomedicine has put zirconia under the spotlight, it is a bio-inert, refractory grade metal-oxide that shares many of the characteristic properties that make up valvemetal/metal-oxide based implants favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Besides Ti, Zirconium (Zr) or Zirconia (ZrO 2 ) is emerging as a popular dental implant material choice attributed to its reduced affinity to bacterial plaque, appropriate mechanical properties, white colour and non-magnetic nature [14]. In a pioneering study, Chopra et al reported nano-engineering of curved and micro-rough Zr surfaces via electrochemical anodization to fabricate various nanotopographies [15]. Briefly, by optimizing anodization conditions, dental implant/abutment relevant surfaces were modified with ZrO 2 nanotubes, nanocrystals or nanopores, bringing anodization of dental implants closer to clinical translation.…”
mentioning
confidence: 99%